STRATEGI MENINGKATKAN KESADARAN POLITIK DAN MENOLAK MONEY POLITIC PEMILIH PEMULA PADA PILKADA KOTA MALANG - Dody Setyawan; Ignatius Adiwidjaja (REFORMASI, 2013)
First time voter is one of the important factors that cannot be ignored by political party in gain votes in the upcoming 2014 election. Estimated that there are about 22 million voters who will have the right to vote for the first time in the 2014 elections[5]. Characteristics of first time voters, who “still fragilea” or not independent in the decision to choose independently, become a space that must be touched by the political parties, which is suspected through money politics approach. Money politics although relatively hard to find evidence of cheating, but there is and can be traced through the testimony of the receiver[5]. Strategy to increase political awareness and consciousness reject money politics first voters in elections and the 2014 presidential election, it is the primary and principal purpose of this study. This study use qualitative methods, with phenomenological perspective. The way to collecting data is by using interviews, and determination of informants using purposive sampling technique and subsequent snowball sampling. Data analysis performed by multilevel methods, namely: Group analysis of the content of the interview, group theme analysis, group case analysis, and groups supporting data. Analysis of the results of studies is using theoretical approaches Miles & Huberman. For the validity of the data, this study is using triangulation and peer debriefin. The result of the studi are; intensive socializations to high school are required because most of the voters are still in school, and we need to provide politic corner to make the voters easier in getting the election information.